Pengaruh Ketimpangan Kesejahteraan terhadap Tingkat Kemiskinan di Pulau Sumatera - Muhammad Khairul Nawwari; Anna Yulianita; Syawal Novaliansyah; Muhammad Rizky Putra Ramadhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of welfare inequality on poverty levels on the island of Sumatra. Welfare inequality is measured using the Gini Index, while poverty levels are measured by the percentage of the poor population at the provincial level. This study uses a quantitative method with a panel data approach covering ten provinces on the island of Sumatra during the period 2020–2024. The analytical techniques used include panel data regression with fixed and random effects models, as well as classical assumption testing to ensure model validity. The results show that welfare inequality has a positive and significant effect on poverty levels, meaning that increasing inequality in income distribution tends to increase the number of poor people. This finding indicates that uneven economic growth can worsen the welfare of the community, especially low-income groups. Therefore, more inclusive and sustainable development policies are needed, particularly in increasing equitable access to education, health services, and productive employment opportunities to reduce inequality and poverty levels on the island of Sumatra.